RESEARCH CAPABILITY OF DEPED TEACHERS: BASIS FOR EXTENSION PROGRAM OF THE UNIVERSITY - Ariel A. Bongco; Maila M. Capulong; Cesar C. Gonzales (International Interdisciplinary Conference on Sustainable Development Goals, 2023)
The contemporary world poses numerous challenges to the concept of research capacity and capability across various academic disciplines. The Department of Education, with its adoption of the Basic Education Research Agenda (DepEd Order No. 39, s. 2016) emphasizes the role of the teachers to generate new knowledge, focus on relevant education issues, and maximize available resources for research. The study aims to assess the research capabilities of the 44 teachers of the SDO Balanga City in the following areas: basics of research, research proposal writing, conducting the research proper, use of statistical tools analysis and interpretation of data, formulating conclusion and recommendation, research report writing, thesis advising, and paneling in thesis oral examination. The study follows the quantitative research method, specifically descriptive evaluative research. This design is to carefully appraise the worthiness of the current study. Overall, the teachers have very good research capabilities. They believed, in general, they have working research knowledge, which makes them confident in writing and teaching research. On the other hand, the teachers manifested the need for training on thesis advising having the lowest rating, which is only indicated as “good”, followed using statistical software. In most of the areas where the teachers rated themselves as “very good”, the researcher still believes that a support system may still be given since the educational sector always strives for excellence. The end goal of this research undertaking is to collaborate with the SDalanga City through extension services of the university to address the identified problems